Prilidiano Pueyrredón - Luna, Félix; Amigo, Roberto; Giunta, Patricia (Proyecto cultural: Artistas del Mercosur, 1999)
Ensayo histórico de: Luna, Félix. Estudios críticos de: Amigo, Roberto y Giunta, Patricia Laura